The Cost of Ill Health - Heather Holt (New Zealand Government, The Treasury, 2010)
This paper aims to quantify some of the costs associated with ill health in New Zealand. The main focus is in estimating indirect costs as opposed to direct health care expenditure costs. In particular, it estimates the cost of absenteeism, presenteeism, working less and not working at all owing to ill health. Around 1,196,200 working age, non-students are estimated to contribute to one or more of the components of indirect costs estimated. That is 61.8% of all working age, non-students. Evaluated at the average full-time pay rate, the estimated hours lost equate to 4.127 billion to 11.563 billion in 2004/05; 2.7% to 7.6% of Gross Domestic Product (GDP). The considerable range in the cost estimate is owing to the large range of the presenteeism estimate as a result of having to use a variety of methods and assumptions to obtain estimates. This illustrates what a difficult concept presenteeism is to estimate, and how sensitive estimates are to the assumptions made. Owing to the assumptions made, the estimate of absenteeism is likely to miss a large group of absenteeism and thus the estimate is likely to be at most a lower bound. Despite this under-coverage, and in line with other research, it seems likely that absenteeism will be generally smaller in size than presenteeism. Working fewer hours, or not working at all, owing to ill health are estimated to affect widely different numbers of people; 458,500 and 42,300 respectively. However, in terms of costs their impact is more similar; 1.442 billion and 1.755 billion respectively. Taking the estimate of presenteeism nearest the mid-point of the range, indirect costs are estimated to be 7.483 billion; 4.9% of GDP. Presenteeism accounts for 55% of this cost, not working 23%, working less 19% and absenteeism just 3%. The only component of direct costs estimated is hospital inpatient appointments, owing to data limitations and the particular focus of this study. Around 1,301,700 people are estimated to be affected by hospital inpatient costs or indirect costs. In monetary terms the total cost of the considered components is estimated to be 5.417 to 12.853 billion; 3.6% to 8.5% of GDP.
Keywords: J22; I10; 330; Health; Productivity; Absenteeism; Presenteeism; Labour Force Participation; Krankheit; Soziale Kosten; Erwerbstätigkeit; Neuseeland